Avocados in Kenya: What’s holding back smallholder farmers - Amare, Mulubrhan (The Conversation, 2020)
Kenya is the world’s third largest producer of avocados. It’s also Kenya’s leading fruit export, accounting for nearly one-fifth of its total horticultural exports. But Kenya only exports 10% of its total avocado production. By comparison, Chile exports 55% and South Africa exports 60%. Avocado is grown in several parts of Kenya and about 70% of avocado production is by small-scale growers. They grow it for subsistence, local markets, and export purposes. The avocado export market in Kenya is dominated by five major exporters: Kakuzi, Vegpro, Sunripe, Kenya Horticultural Exporters, and East African Growers. These companies source their avocados primarily from smallholder farmers, although some firms also source from larger growers or own plantations. In a new study we surveyed 790 avocado-farming households in Kenya and analysed what factors get in the way of smallholder farmers participating in export markets. We then looked at the implications this has on their farming businesses. This included labour inputs – such as hired and family labour – farm yields, sales prices, and finally, incomes.